PENERAPAN AKUNTANSI MANAJEMEN DALAM MENUNJANG INOVASI DAN KEUNGGULAN KOMPETITIF PADA PERUSAHAAN JASA DI INDONESIA - Pebrianti, Pebrianti; Komarudin, Mochamad Fahru (Yayasan Education and Social Center, 2025)
This study aims to analyze the implementation of management accounting in supporting innovation and competitive advantage in service companies in Indonesia. The research employs a qualitative approach with a case study strategy, involving finance managers, innovation managers, and operational managers as key informants. Data were collected through in-depth interviews, participatory observation, and company documentation. Thematic analysis was conducted to identify the relationship between management accounting, innovation, and competitive advantage achievement. The results indicate that companies implementing digital-based management accounting can provide accurate and timely information, support strategic decision-making, and enhance innovation effectiveness. Integration of management accounting with innovation strategies enables companies to respond quickly to market changes, improve operational efficiency, and strengthen customer satisfaction. These findings confirm that management accounting serves as a strategic instrument to drive sustainable innovation and achieve competitive advantage in the service sector.